DEVELOPING CRITICAL THINKING SKILLS THROUGH ENGLISH LITERATURE IN UZBEK CLASSROOMS - Zokirova Marjona Xislatjon qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Annotation: This paper explores how English literature can be used as an effective tool to develop critical thinking skills among students in Uzbek classrooms. It discusses the role of literary texts in encouraging analytical reading, interpretation, and reflection. The study examines various pedagogical approaches to integrating literature into the curriculum to foster deeper cognitive engagement. It highlights challenges faced by teachers and learners and proposes strategies to overcome them, emphasizing the importance of critical literacy in language education.